2003
DOI: 10.1063/1.1571221
|View full text |Cite
|
Sign up to set email alerts
|

Controllability properties for finite dimensional quantum Markovian master equations

Abstract: Various notions from geometric control theory are used to characterize the behavior of the Markovian master equation for N-level quantum mechanical systems driven by unitary control and to describe the structure of the sets of reachable states. It is shown that the system can be accessible but neither small-time controllable nor controllable in finite time. In particular, if the generators of quantum dynamical semigroups are unital, then the reachable sets admit easy characterizations as they monotonically gro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
160
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(162 citation statements)
references
References 19 publications
2
160
0
Order By: Relevance
“…To our knowledge, this is the first instance of open quantum system control through the bath parameters, and not via the subsystem Hamiltonian [22,23]. This approach, which might prove very fruitful in the field of quantum information, is still in a very preliminary stage; further developments are presently under study and will be reported elsewhere.…”
Section: Environment Induced Entanglement Generationmentioning
confidence: 99%
“…To our knowledge, this is the first instance of open quantum system control through the bath parameters, and not via the subsystem Hamiltonian [22,23]. This approach, which might prove very fruitful in the field of quantum information, is still in a very preliminary stage; further developments are presently under study and will be reported elsewhere.…”
Section: Environment Induced Entanglement Generationmentioning
confidence: 99%
“…[50,51]. Considering the inner product X, Y = tr(X † Y ), we can find the following matrix basis for all two-qubit matrices:…”
Section: Appendix A: Derivation Of the Maximum Concurrence And Fidelitymentioning
confidence: 99%
“…The corresponding models are called coherent control methods as the controls enter the coherent part of the dynamics, and their properties have been widely investigated. In particular, it has been proven that quantum states cannot be purified by using coherent control, both in closed and open systems dynamics, whether the controls are fixed at the beginning [11,12]. To overcome this difficulty, several solutions have been proposed, as the use of an indirect measurement, performed on the system.…”
mentioning
confidence: 99%